Grid connected solar water pumping system - Reddy, Mula Sreenivasa; Raja, Banda Srinivas; Kiranbabu, Movva Naga Venkata; Parvez, Muzammil; Inthiyaz, Syed; Prakash, Nelaturi Nanda; Rajanna, Bodapati Venkata; Surendher, Guntukala (Institute of Advanced Engineering and Science, 2025)
A grid-connected solar water pumping system (SWPS) uses solar power to pump water while simultaneously drawing power from the grid when necessary. These systems can benefit farmers in a variety of ways, including reliable power, lower electric bills, increased income, and improved economic viability. This study explores a solar photovoltaic (SPV) water pumping system designed to function with a single-phase distribution network. It utilizes an induction motor drive (IMD) and incorporates an advanced power-sharing technique for optimal performance. In addition to transferring power from SPV to IMD, a DC-DC boost converter functions as a grid interface and power factor adjustment device. Maximizing the power extracted from the SPV array is critical for optimizing its utilization. To do this, a control mechanism based on incremental conductance is implemented to track maximum power points. Simultaneously, the IMD connected to the power source inverter is regulated using a simple volt/frequency approach. The suggested system, which includes standalone, grid-interfaced, and mixed-mode situations, is developed and validated in a lab.